Grupo de estudo/discussão como estratégia formadora de autonomia docente em professores de física - Araya, Ana Maria Osório [UNESP]; Silva, João Ricardo Neves da [UNESP]; Souza Filho, Moacir Pereira de [UNESP]; Lino, Alex (My University, 2011)
This work is intended to promote a reflection about the forms of work in groups for continuous training of teachers. Based on the hypothesis that the groups of study / discussion of specific topics in physics can have very effects significant and recommended by the literature, we based on the propositions of the educator José Contreras Domingo about autonomy of teachers and we does a report of an experience with group of continuing education in which they succeeded in developing the characteristics of autonomy of teachers in a job with physics teachers who participate in a group of study / discussion of topics of Modern and Contemporary Physics. In this way presents arguments relating the autonomy of teachers with the teacher continuing education and presents the report of a group of training teachers of physics who works along these lines.

Este trabalho objetiva promover uma reflexão acerca das formas de trabalhar em grupos de formação continuada de professores, visando o desenvolvimento de características propostas pela pesquisa acadêmica como importantes em professores. Baseados na hipótese de que os grupos de estudo/discussão de tópicos específicos de Física podem surtir efeitos significativos e recomendados pela literatura da área de Ensino de Física, este trabalho tem como principal referencial teórico a obra de José Contreras Domingo, sobre autonomia docente. Apresenta-se o relato de uma experiência de grupo de formação continuada no qual se obteve sucesso em desenvolver as características de autonomia docente, em um trabalho com professores de Física que participam do grupo. A metodologia de trabalho do grupo é o estudo/discussão de tópicos de Física Moderna e Contemporânea. Apresenta-se argumentos que relacionam a autonomia docente e a formação continuada de professores nesta forma de capacitação.
The group of study/discussion as a strategy to training of autonomy in physics teachers
Keywords: Continuing formation of teachers; Autonomy of teachers; Groups of study/discussion; Modern and contemporary physics in high school; Formação continuada de professores; Autonomia docente; Grupos de estudo/discussão; Física moderna e contemporânea no ensino médio